Comparative Study of Minimally Invasive Plate Osteosynthesis (MIPO) and Intramedullary Nailing (IMN) for Treating Extraarticular Distal Tibial Fractures: Clinical and Radiological Outcomes - Kaya, Oguz; Tosun, Haci Bayram; Kurum, Hueseyin; Serbest, Sancar; Uludag, Abuzer; Ayas, Orhan (Int Scientific Information, Inc, 2023)
Background: Treatment of extra-articular distal tibial fractures is problematic owing to limited soft tissue cover, poor vascularity of the location, and adjacency to the ankle, and thus continues to be controversial. This study aimed to compare clinical and radiological outcomes in 69 patients with extra-articular distal tibia fractures treated with minimally invasive plate osteosynthesis (MIPO) and an interlocking intramedullary nail (IMN).Material/Methods: Sixty-nine patients, with mean of age 39.8 +/- 18.3 years, were retrospectively evaluated. Thirty-five patients were treated with IMN, and 34 patients were treated with MIPO. Clinical and radiological outcomes were evaluated.Results: The average follow-up was 13.3 +/- 6 months and union time was 16.2 +/- 5.4 weeks. Nonunion was observed in only 4.3% of patients treated with MIPO (P=0.114). Non-acceptable malalignment of extremity was observed in 4.3% of patients with IMN and 7.2% of patients with MIPO. There were no significant differences in union time, nonunion, surgical timing, operating time, malalignment, and complications between groups (P>0.05). The mean American Orthopaedic Foot and Ankle Society (AOFAS) surgery score was 95.8 +/- 5 in IMN and 91.9 +/- 14.3 in MIPO. AOFAS, Tenny-Wiss radiological, and Ovadia-Beals clinical scores were better in IMN than MIPO (P=0.019, P=0.03, P=0.02, respectively). Mean time of full weight-bearing and of return to daily life with IMN was significantly shorter than with MIPO (P<0.001).Conclusions: IMN and MIPO methods are reliable and effective methods with similar good results in the surgical treatment of extra-articular distal tibia fractures. However, IMN may be preferred for early full weight-bearing and early return to daily life (P<0.001).
Keywords: Fracture Fixation; Intramedullary; Minimally Invasive Surgical Procedures; Tibial Fractures; Intra-Articular Fractures; Fractures, Bone